TRANSFORMASI SAMPAH RUMAH TANGGA PRODUK PENGOLAHAN SAMPAH MENJADI ECOBRICK DAN KOMPOS - Nurhannifah Rizky Tampubolon; Yufitriana Amir; Dwi Ningtias; Afni Ramadhani; Dona Armelia Putri; Puja Permata Nur; Dedi Kristian Gulo; Camilla Devania; Tiara Asyifa Putri; Salma Mahiroh; Gustika Wulandari; Nisa Destiana; Rafiq Hidayah; Dismawati (Institut Kesehatan Yarsi Mataram, 2026)
Household waste management remains a challenge in urban areas, including Bencah Lesung Village. The increasing volume of waste without proper management can negatively impact the environment and public health. A study found thatmost residents of RW 6 still burn waste as the primary method of reducing household waste volume. This activityaims to improve the knowledge and skills of RW 6 residents in processing organic waste into compost and inorganic waste into ecobricks as an environmentally friendly waste management alternative. The implementation method was carried out through education, demonstrations, and direct assistance to residents, with pre-test and post-test evaluations on 15 respondents. The results of the activity showed an increase in community understanding of sustainable waste management and the ability to make ecobricks and compost. The average pre-test score of 7.27 increased to 9.20 in thepost-test, with an increase in knowledge of 33.3% of the 15 respondents. Conclusion, this education, demonstration, and mentoring program was proven to be effective in improving the knowledge and skills of the RW 6 community in sustainable waste management through composting and ecobrick production as an effort to create a cleaner and healthier environment.This activity is expected to be a concrete step towards a clean, healthy, and efficient environment in RW 6, and has been proven to increase community knowledge and skills in sustainable waste management.